A case of Artery of Percheron infarct caused by Dengue virus encephalitis - Verma, Archana; Garg, Pragati; Mishra, Ashutosh Kumar (Nepal Journal of Neuroscience, 2022)
In this communication, we describe a patient with dengue virus encephalitis who presented with fever and sudden onset bilateral oculomotor nerve involvement with left side hemi paresis, MRI showing bilateral thalamus and midbrain involvement (artery of Percheron infarct).